234 Echocardiographic visualization of retroaortic anomalous coronary artery. (8th December 2021) - Bruno, Noemi; Ferrari, Ilaria; Pelliccia, Francesco; Gaudio, Carlo; Monzo, Luca
Abstract: A 65-year-old female was admitted to our hospital for sudden onset of typical chest pain at rest lasting few minutes. Her medical background included systemic hypertension, type 2 diabetes, dyslipidaemia, and mild obesity. Upon arrival in the emergency room, the electrocardiogram didn't reveal signs of acute myocardial ischaemia and serial cardiac troponin T measurements were persistently negative. A transthoracic echocardiogram (TTE) was performed, showing mild ventricular hypertrophy, no regional wall motion abnormalities, and a preserved left ventricular ejection fraction. A highly echogenic tubular structure, located slightly on the atrial side of the atrioventricular groove was noted in multiple apical views. Its tubular shape was suggestive of a vascular structure, but its location was atypical for a normal vessel; indeed its persistence in more than an echocardiographic plane excluded an artefact. According to patient's clinical history and her high cardiovascular risk profile she was referred for coronary angiography, demonstrating no critical stenosis but an anomalous aortic origin of a coronary artery (AAOCA) from the inappropriate sinus of Valsalva: the left main coronary artery (LMCA) arose from the right coronary cusp and then took a caudal posterior loop running posterior to the aortic root. In light of these findings we could associate the tubular structure seen at TTE to the retroaortic course of LMCA, a finding recently described as retroaortic anomalous coronary (RAC) sign. Among AAOCA, the retroaortic course of the LMCA is an uncommon diagnosis in adults, and its association with a single coronary origin is extremely rare. Although it has been usually considered a benign clinical entity, it is associated with an increased risk in morbidity and mortality during valve surgery. The presence of RAC sign at TTE was demonstrated to be highly suggestive of an anomalous coronary artery (specificity 93.9%) and strongly associated with retroaortic LMCA course at computed tomography angiography.